ANTIMICROBIAL PEPTIDE P34 INFLUENCES GENE EXPRESSION OF LISTERIA MONOCYTOGENES GROWING IN SOFT CHEESE - Vaucher, Rodrigo De Almeida; Giongo, Janice Luehring; RECH, VIRGINIA CIELO; Santos, Roberto Christ Vianna; Lopes, Leonardo Quintana S.; EBLING, MARCIA; DELAMEA, MATHEUS; Silva, Aleksandro Schefer; Brandelli, Adriano (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To evaluate whether antimicrobial substances produced by autochthonous lactic acid bacteria (LAB) from Minas Frescal cheese are able to enhance the activity of bacteriocin P34 against Listeria monocytogenes and investigate the influence of P34 in specific gene expression of this bacterium after the inoculation in Minas Frescal cheese. Methods: Bacillus sp. P34 and L. monocytogenes ATCC 7644 were used in this study. The antimicrobial peptide P34 was purified and applied (0, 800 or 6400 AU/ml) to cheese surface before inoculation with L. monocytogenes. Antimicrobial activity and synergism were detected using the agar diffusion technique. Expression levels of D-Alanine-D-alanyl carrier protein ligase (dltA), Putative phospholipid lysinylation (Imo 1695) and EIIABMan of mannose-specific PTS (mptA) mRNAs in bacteriocin-treated L. monocytogenes growing in Minas Frescal cheese were determined using real-time PCR. Results: The peptide P34 showed increased antilisterial activity when combined with culture supernatants of some selected LAB isolated from Minas Frescal cheese. The addition of peptide P34 to cheese caused a decrease of up to 3 log cycles in viable counts of artificially inoculated L. monocytogenes. The influence of peptide P34 on the expression of genes associated with components of the cell surface of L. monocytogenes was investigated by real-time PCR. A significant increase in the expression of the genes dltA, Imo 1695 and mptA was observed after 96 h in the presence of peptide P34. Conclusion: These results suggest that the peptide P34 influences the expression of genes involved in D-alanylation of teichoic acids and lipoteichoic acids and lysination of the cell membrane of phospholipids.